Promotion of cell membrane fusion by cell-cell attachment through cell surface modification with functional peptide-PEG-lipids. (September 2020) - Yoshihara, Akifumi; Watanabe, Sayumi; Goel, Isha; Ishihara, Kazuhiko; Ekdahl, Kristina N.; Nilsson, Bo; Teramura, Yuji
Abstract: Cell fusion is a fundamental event in various biological processes and has been applied to a number of biotechnologies. However, cell fusion efficiency is still low and strongly depends on cell lines and skills, though some improvements have been made. Our hypothesis is that two distinct cell membranes need to be brought together for cell membrane fusion, which is important for mimicking cell fusion in vitro . Here, we aimed to improve the homogeneous and heterogeneous cell fusion efficiency using a cell-cell attachment technique. We modified cellular membranes with two distinctive poly(ethylene glycol)-lipids (PEG-lipids) carrying oligopeptide, three repeated units of the EIAALEK and KIAALKE sequences (fuE3 and fuK3, respectively), which induce cell-cell attachment. The ratio and area of cell-cell attachment can be controlled through surface modification with fuE3-and fuK3-PEG-lipids by changing the number of each incorporated peptide. By combining this technique with the PEG-induced method, the cell fusion efficiency was significantly improved for homogeneous and heterogeneous cell fusion compared to conventional PEG-induced methods. For homogeneous CCRF-CEM cell fusion, the efficiency increased up to 64% from the 8.4% with the PEG-induced method. In addition, for heterogeneous cell fusion of myeloma cells and splenocytes, the efficiency increased up to 18% from almost zero. Thus, cell membrane fusion could be promoted effectively between closely contacted cell membranes induced by the cell-cell attachment technique.